Magmatism on rift flanks: Insights from ambient noise phase velocity in Afar region. Issue 7 (3rd April 2015) - Korostelev, Félicie; Weemstra, Cornelis; Leroy, Sylvie; Boschi, Lapo; Keir, Derek; Ren, Yong; Molinari, Irene; Ahmed, Abdulhakim; Stuart, Graham W.; Rolandone, Frédérique; Khanbari, Khaled; Hammond, James O. S.; et al.
Abstract During the breakup of continents in magmatic settings, the extension of the rift valley is commonly assumed to initially occur by border faulting and progressively migrate in space and time toward the spreading axis. Magmatic processes near the rift flanks are commonly ignored. We present phase velocity maps of the crust and uppermost mantle of the conjugate margins of the southern Red Sea (Afar and Yemen) using ambient noise tomography to constrain crustal modification during breakup. Our images show that the low seismic velocities characterize not only the upper crust beneath the axial volcanic systems but also both upper and lower crust beneath the rift flanks where ongoing volcanism and hydrothermal activity occur at the surface. Magmatic modification of the crust beneath rift flanks likely occurs for a protracted period of time during the breakup process and may persist through to early seafloor spreading.